Gossypiboma as a rare cause of abdominal mass. (20th November 2014) - Yildirim, Afra; İmamoğlu, Hakan and Erzurumdağ, Aslı and Doğan, Serap
Abstract : Gossypiboma is a reaction to a foreign body/object left accidentally inside a patient as a consequence of surgery. This phenomenon may be overlooked due to its rarity or under-reported due to possible repercussions. We report an intra-abdominal gossypiboma that was misdiagnosed on ultrasound, and discuss its radiological findings.